Prevalence, Pattern, Risks Factors and Consequences of Antibiotic Resistance in COPD: A Systematic Review. (2nd November 2021) - Smith, Daniel; Gill, Arran; Hall, Lewis; Turner, Alice M.
Abstract: A concern of antibiotic use in chronic obstructive pulmonary disease (COPD) is the emergence and propagation of antimicrobial resistance (AMR). A systematic review was conducted to determine prevalence, pattern, risk factors and consequences of AMR in COPD. Bibliographic databases were searched from inception to November 2020, with no language restrictions, including studies of any design that included patients with COPD and reported prevalence and pattern of AMR. 2748 unique titles and abstracts were identified, of which 63 articles, comprising 26, 387 patients, met inclusion criteria. Forty-four (69.8%) studies were performed during acute exacerbation. The median prevalence of AMR ranged from 0–100% for Pseudomonas aeruginosa, Moraxella catarrhalis, Klebsiella pneumoniae and Acinetobacter baumannii . Median resistance rates of H influenzae and S pneumoniae were lower by comparison, with maximum rates ≤40% and ≤46%, respectively, and higher for Staphylococcus aureus . There was a trend towards higher rates of AMR in patients with poorer lung function and greater incidence of previous antibiotic exposure and hospitalisation. The impact of AMR on mortality was unclear. Data regarding antimicrobial susceptibility testing techniques and the impact of other risk factors or consequences of AMR were variable or not reported. This is the first review to systematically unify data regarding AMR in COPD. AMR is relatively common and strategies to optimise antibiotic use could be valuable to prevent the currently under-investigated potential adverse consequences of AMR. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2021.2000957 .